The time series study on the temperature effect over Penang Island using GIOVANNI / Kamal Fiqre Md Kamaludin, Dr. Muzafa Jumidali and Fathinul Najib Ahmad Sa'ad - Md Kamaludin, Kamal Fiqre; Jumidali, Muzafa; Ahmad Sa'ad, Fathinul Najib (2020)
NASA GIOVANNI is an advanced technology of remote sensing system. It is able to provide with Earth Science information within only a few minutes. The focus of this study is to obtain a reliable information via NASA GIOVANNI regarding the temperature trend in Penang Island, Malaysia, from year 2016 to 2018 and also to verify the validity and reliability of the data obtained from NASA GIOVANNI and therefore being able to replace with the conventional method of using AccuWeather. From the system, MODIS Aqua is selected as it is the most suitable satellite among other to capture the temperature reading at the desired area. The data obtained from AccuWeather are mostly accurate and clear even though there are several limitations regarding the parameter involved as it is quite general. Meanwhile the temperature data obtained from NASA GIOVANNI are more specific and detailed as it consists of several parameters. For example, NASA GIOVANNI is capable of accessing the sea surface and land surface temperature for the desired location. Apart from that, NASA GIOVANNI also able to separate between daytime and nighttime temperature data. After obtaining both data from NASA GIOVANNI and AccuWeather, an effective comparison is made via cross validation or to be exact, linear regression. From the graph of linear regression, R-Squared value can be calculated and hence can determine the correlation of both data. From the R-Squared calculations, the values calculated are 0.75 for year 2016, 0.65 for year 2017 and 0.71 for year 2018. According to the R-Squared value, it is concluded that the temperature data from NASA GIOVANNI is having a positive and strong correlation with AccuWeather as the values are exceeding 0.5 for each year. Therefore, the temperature data via NASA GIOVANNI is possible to obtained and also the obtained temperature data are almost as accurate as AccuWeather